Hubungan Tingkat Pengetahuan dan Persepsi terhadap Kesediaan Menggunakan Telefarmasi pada Mahasiswa Farmasi - Christina Angelica Stephani Sianturi; Lucia Vita Inandha Dewi; Carolina Eka Waty (Jurnal Farmasi Indonesia, 2025)
Telepharmacy is the use of information and communication technology to provide long-distance services between patients and pharmacists. The success factor for implementing telepharmacy is good willingness by pharmacists today and in the future. Assessment of the level of knowledge and perception of pharmacy students is very important as a determinant of their willingness in telepharmacy services because good knowledge and perception of students can increase their willingness to provide telepharmacy services as their future work. This study is a descriptive study using a questionnaire. The population in this study were Pharmacy S1 students in semesters 6 and 8 totaling 323 students. The results of the study obtained a good level of knowledge, a positive level of perception, and a high level of willingness to provide telepharmacy services. In the Chi-square test, there was a relationship between the level of knowledge and perception of students' willingness to provide telepharmacy services in the future with a p-value of 0.011 and 0.000 (sig <0.05) indicating that good knowledge and positive perceptions are related to high student willingness.